Improving Student Learning Motivation After the Pandemic - Didik Himmawan; Siti Aisyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of the classical guidance activity entitled Improving Student Learning Motivation is to be able to re-increase students' enthusiasm for learning face-to-face at school. The approach used in the work program in conveying problem solving is by collecting data through in-depth interviews with objects in the service, also by conducting Observations or observations which are a way of collecting data by observing ongoing activities. The problems in the school are the lack of supporting tools for teaching and learning and students' motivation to learn has decreased during the pandemic. The results of this activity are that Education is a very important thing in a country. With education, a young generation will be created who can shape this country to be better than before. The activity consists of three stages, namely Planning, Implementation, and Evaluation. Before implementing the delivery of the material, the team made a plan for implementing this program. Students are given an understanding of the application of the importance of enthusiasm for learning, managing time and enthusiasm for learning and motivating students to continue learning even in any condition.